93.6k views
1 vote
Find the value of this expression if x=-6 x^2-6/x-4

User Archbishop
by
5.3k points

2 Answers

4 votes

Answer:

x=−0.825789

Explanation:

x=(−6x3−4x−6)/x

Step 1: Multiply both sides by x.

x2=−6x3−4x−6

x2−(−6x3−4x−6)=−6x3−4x−6−(−6x3−4x−6)(Subtract -6x^3-4x-6 from both sides)

6x3+x2+4x+6=0

(Use cubic formula)

x=−0.825789

User Fidel Castro
by
5.0k points
4 votes

Answer:

- 3

Explanation:

Substitute x = - 6 into the expression


((-6)^2-6)/(-6-4)

=
(36-6)/(-10) =
(30)/(-10) = - 3

User Malachiasz
by
5.9k points